Discordant Marker Expression Between Invasive Breast Carcinoma and Corresponding Synchronous and Preceding DCIS. (November 2019) - Visser, Lindy L.; Elshof, Lotte E.; Van de Vijver, Koen; Groen, Emma J.; Almekinders, Mathilde M.; Sanders, Joyce; Bierman, Carolien; Peters, Dennis; Hofland, Ingrid; Broeks, Annegien; van Leeuwen, Flora E.; Rutgers, Emiel J. Th; et al.
Abstract : Ductal carcinoma in situ (DCIS) is considered a potential precursor of invasive breast carcinoma (IBC). Studies aiming to find markers involved in DCIS progression generally have compared characteristics of IBC lesions with those of adjacent synchronous DCIS lesions. The question remains whether synchronous DCIS and IBC comparisons are a good surrogate for primary DCIS and subsequent IBC. In this study, we compared both primary DCIS and synchronous DCIS with the associated IBC lesion, on the basis of immunohistochemical marker expression. Immunohistochemical analysis of ER, PR, HER2, p53, and cyclo-oxygenase 2 (COX-2) was performed for 143 primary DCIS and subsequent IBC lesions, including 81 IBC lesions with synchronous DCIS. Agreement between DCIS and IBC was assessed using kappa, and symmetry tests were performed to assess the pattern in marker conversion. The primary DCIS and subsequent IBC more often showed discordant marker expression than synchronous DCIS and IBC. Strikingly, 18 of 49 (36%) women with HER2-positive primary DCIS developed an HER2-negative IBC. Such a difference in HER2 expression was not observed when comparing synchronous DCIS and IBC. The frequency of discordant marker expression did not increase with longer time between primary DCIS and IBC. In conclusion, comparison of primary DCIS and subsequent IBC yields different results than a comparison of synchronous DCIS and IBC, in particular with regard to HER2 status. To gain more insight into the progression of DCIS to IBC, it is essential to focus on the relationship between primary DCIS and subsequent IBC, rather than comparing IBC with synchronous DCIS. Abstract : Supplemental Digital Content is available in the text.